Francisci a Mesgnien Meninski'nin Thesaurus'una göre 17. yüzyıl Osmanlı Türkçesi deyimleri - Çelebi, Nurcan (My University, 2019)
Gerçek anlamının dışında kullanılıp anlama akıcılık katan toplumun benimsemiş olduğu söz öbeklerine deyim denir. Çekici bir anlatım özelliği bulunan deyimler en az iki sözcükten oluşmakta ve kalıp olarak kullanılmaktadırlar. Günlük hayatta özellikle konuşma dilinde çok sık kullandığımız deyimler, dilimizin zenginliğini gösteren en önemli kelime gruplarının başında gelmektedir. Deyimler birden fazla yapısal özellik göstermektedirler. Bazı deyimler, söz öbekleri ve cümle yapılarında kalıplaşmaktadırlar.Çalışmada Francisci a Mesgnien Meninski’nin Thesaurus’undan yola çıkılarak 17.yy Osmanlı Türkçesi deyimleri derlenerek incelenmiştir.İnceleme kısmında deyimler, söz öbekleriyle kurulan deyimler ve cümle biçiminde kurulan deyimler olarak iki kısımda incelenmiştir.Metindeki deyimler Meninski’nin çeviri yazıda kullandığı işaretler ve bizim bunların yerine kullandığımız işaretlerle birlikte yazılmıştır. Transkripsiyonu yapılan deyimlerin anlamları da açıklanarak Türkiye Türkçesi’ne aktarılmıştır.Son olarak dizin kısmında

Phrases adopted by the society that adds fluency to the meaning beside its real meaning are called idioms. Idioms with an attractive narrative feature consist of at least two words and are also used as a template. The idioms used frequently in daily life, especially in the spoken language, are among the most important group of words showing the richness of our language. Idioms show more than one structural features. Some idioms are molded together with phrases and sentence structures.In this study, 17th century Ottoman Turkish idioms were compiled and examined from the Thesaurus of Francisci a Mesgnien Meninski.In the analysis part, idioms are examined in two parts as idioms established with phrases and idioms with the sentence form.The idioms in the text are written together with the signs that Meninski uses in the translational texts and the signs that are used. The meanings of transcription was transferred to the statementswith a short briefing in Turkish.Finally, in the index section, the constituent words and compound words that form the statements are indexed.
Keywords: 17.yy Osmanlı Türkçesi Deyimleri; 17th century Ottoman Turkish Idioms; History and criticism; Meninski; Tarih ve eleştiri; Thesaurus; Turkish literature; Türk edebiyatı